Friction nano-generator based on fish scale gelatin and silk fibroin composite film and preparation method thereof

By combining fish scale gelatin and silk fibroin composite film with PDMS film, efficient, low-cost, and environmentally friendly friction nanogenerators were prepared, which solved the problems of low efficiency, high cost and poor environmental adaptability of existing friction electrical materials, and achieved high-performance energy collection suitable for wearable electronic devices and Internet of Things technology.

CN119552587APending Publication Date: 2025-03-04QINGDAO YUANTONG MEDICAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411713995.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Existing triboelectric materials have problems such as low efficiency, high cost and poor environmental adaptability, and it is difficult to meet the energy needs of wearable electronic devices and IoT technology.

Method used

A friction nanogenerator based on a composite film of fish scale gelatin and silk fibroin was used to regulate the mechanical and chemical properties of the film by doping heterophasic templates such as silk fibroin, and TENG was prepared in combination with PDMS film.

Benefits of technology

It realizes efficient, low-cost, environmentally friendly energy collection technology, significantly improves the output electrical performance of friction nanogenerators, including voltage, current and power density, and meets the needs of wearable devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552587A_ABST
    Figure CN119552587A_ABST
Patent Text Reader

Abstract

The invention provides a friction nano-generator based on a fish scale gelatin and silk fibroin composite film and a preparation method thereof, waste fish scales and natural silkworm cocoons are processed into the composite film through multiple steps of cleaning, dissolving, solution dialysis and the like, the composite film and a polydimethylsiloxane (PDMS) film are used as friction pairs, and the friction nano-generator based on the fish scale gelatin and silk fibroin composite film is obtained. The friction nanometer generator realizes operation in a vertical contact-separation mode, and is made into an efficient friction nanometer generator in combination with an elastic structure design. In addition, by doping the high-dielectric-constant nanoparticles, the electric output performance of the friction positive electrode material is remarkably improved. The composite film has good thermal stability, hydrolysis resistance, excellent tensile strength and repeated bending performance, effectively overcomes the technical problems that existing fish scale gelatin films are generally poor in mechanical property and easy to redissolve in water, and has the advantages of being low in cost, easy to prepare, high in flexibility, good in biocompatibility and stable and excellent in output performance. The method is suitable for being applied to wearable electronic equipment and the Internet of Things technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nano energy, in particular to a device for collecting mechanical energy and converting it into electrical energy, and specifically to a friction nano generator based on a fish scale gelatin and silk fibroin composite film and a preparation method thereof. Background Art

[0002] With the rapid development of wearable electronic devices and Internet of Things technology, the demand for new energy sources is growing. Traditional energy harvesting technologies usually have problems such as low efficiency, high cost and poor environmental adaptability. Therefore, it is particularly important to develop an efficient, low-cost and environmentally friendly energy harvesting technology. In 2012, Academician Wang Zhonglin first proposed the friction nanogenerator (TENG). As a new type of nano energy harvesting device, it can convert various tiny mechanical energies in the environment into electrical energy, providing self-driven and sustainable energy supply for micro-nano systems. The working principle of TENG is based on the triboelectric effect generated when two materials with different surface friction polarities approach each other, and the induced potential difference formed when they separate, thereby driving electrons to flow in the external circuit.

[0003] Triboelectric materials are a key factor affecting the performance of TENG. Currently, the commonly used materials are mainly organic polymers and their similar materials, which usually contain potentially harmful substances, are expensive, and have poor environmental sustainability and biocompatibility. Therefore, the development of an environmentally friendly and cost-effective triboelectric material is an important direction of current technological development.

[0004] The present invention uses fish scale gelatin extracted from discarded fish scales to prepare a film, aiming to solve the limitations of traditional triboelectric materials. However, pure fish scale gelatin film has deficiencies in mechanical properties and chemical stability, especially the problem of easy hydrolysis when exposed to water.

[0005] In order to overcome these challenges, the present invention regulates the mechanical and chemical properties of fish scale gelatin composite film by doping heterogeneous templates, such as silk fibroin extracted from mulberry silk, to meet the needs of nano friction generators. TENG prepared based on fish scale gelatin / silk fibroin composite film and PDMS film can effectively collect mechanical energy in daily life and provide energy for flexible wearable electronic devices, showing great application potential in the field of self-driven flexible wearable electronic devices.

[0006] In summary, the present invention aims to prepare a high-efficiency, low-cost, and environmentally friendly friction nanogenerator by optimizing the properties of fish scale gelatin composite film, so as to address the limitations of the existing technology and promote the development of wearable electronic devices and Internet of Things technology. Summary of the invention

[0007] The purpose of the present invention is to provide a triboelectric nanogenerator based on fish scale gelatin / silk fibroin composite film and a method for manufacturing the same in order to solve the problems of low energy collection efficiency, high cost, poor environmental adaptability, etc. mentioned in the background technology. The invention aims to provide an efficient, low-cost, and environmentally friendly energy collection technology, which is particularly suitable for the fields of wearable electronic devices and the Internet of Things.

[0008] One of the technical solutions of the present invention is as follows: A friction nanogenerator based on a fish scale gelatin and silk fibroin composite film comprises a first friction material, a second friction material, a first electrode and a second electrode, wherein: The first electrode is covered on the back side of the first friction material, the second electrode is covered on the back side of the second friction material, and the first friction material and the second friction material are stacked face to face to assemble a vertical contact-separation friction nanogenerator (TENG) for collecting mechanical energy and converting it into electrical energy; The first friction material and the second friction material are stacked face to face, and a gap is formed in the middle through the PDMS annular flexible support material; The first friction material is a composite film based on fish scale gelatin / silk fibroin.

[0009] The second friction material is a polydimethylsiloxane (PDMS) film; The first electrode and the second electrode are both made of conductive copper foil tape, and the resistance is 0.01Ω / sq; Preferably, a single-core multi-strand wire is connected between the first electrode and the first friction material, and between the second electrode and the second friction material.

[0010] Preferably, the fish scale gelatin / silk fibroin composite film selected for the first friction material is doped with a heterogeneous material with a high dielectric constant to further improve the output performance of the TENG, including increasing the voltage, current and power density.

[0011] Preferably, the fish scale gelatin / silk fibroin composite film selected as the first friction material and the PDMS film selected as the second friction material have surface microstructures introduced through templates during the preparation process, which significantly increases the surface roughness of the two films.

[0012] The second technical solution of the present invention is as follows: A method for preparing a friction nanogenerator, which is used to prepare a friction nanogenerator based on a fish scale gelatin and silk fibroin composite film, comprises the following specific steps: Step 1: Wash and dry the discarded fish scales for multiple times, weigh 40g of dry fish scales, and then treat the dry fish scales with 0.6M hydrochloric acid for 1h, rinse the treated fish scales with deionized water 10 times and soak them in deionized water for 1h, mix the treated fish scales with 120ml of deionized water and place them in a stainless steel sealed container for hydrolysis, the hydrolysis temperature is 50-120℃, and the hydrolysis time is 3-6h; Step 2: After the fish scales are hydrolyzed and cooled to 25°C, the solid and liquid are separated by a sieve, and the liquid filtrate is centrifuged at 10,000 rpm for 10 minutes to remove the solid residue, so as to prepare a fish scale gelatin aqueous solution; Step 3: After the silk cocoons are cut into pieces, the broken silk cocoons are weighed, deionized water is boiled and sodium carbonate or sodium bicarbonate powder is added, and after the silk cocoons are fully dissolved, the broken silk cocoons are added, and the boiling is maintained for 30 minutes, and the process is repeated three times to ensure that the sericin on the silk surface is fully dissolved, and after the degumming is completed, the silk fibers are rubbed three times with distilled water, and the degummed silk fibers are dried after being cleaned; Step 4: using 9.5M lithium bromide solution to dissolve silk fibers in a 60°C oven for 3 hours to obtain a silk fibroin solution, and then dialyzing the solution, changing the water every 2 hours for 2 days, and finally centrifugally filtering to obtain a clear and transparent silk fibroin solution; Step 5: The fish scale gelatin solution and the silk fibroin solution are mixed in different proportions, and then a plasticizer and high dielectric constant nanoparticles of different concentrations are added thereto and stirred evenly, and the mixed solution is poured into a mold with a microstructure on the surface, and dried at 60° C. for 1 hour to prepare a fish scale gelatin / silk fibroin composite film; Step 6: Attach conductive copper foil tape to the back of the fish scale gelatin / silk fibroin composite film and the PDMS film obtained in step 5 respectively and connect them with single-core multi-strand wires. Place the composite film and the PDMS film opposite to each other, place the PDMS elastomer in the middle as a supporting layer, and assemble them into a friction nanogenerator using a vertical contact-separation mode. Finally, place the assembled generator as a whole in a protective casing.

[0013] Preferably, the plasticizer selected in step 5 includes but is not limited to glycerol.

[0014] Preferably, the high dielectric constant nanoparticles selected in step 5 include but are not limited to barium titanate nanoparticles.

[0015] Preferably, the mold with a microstructure on the surface selected in step 5 is made of materials including but not limited to silicone latex and metal materials, and its microstructure comes from a natural or artificial reverse template.

[0016] Preferably, the protective shell selected in step 6 includes but is not limited to a polyimide (PI) packaging layer.

[0017] Compared with the prior art, the present invention has the following beneficial technical effects: 1. The fish scale gelatin in the present invention has a wide source, low cost, simple preparation method, and is conducive to large-scale production.

[0018] 2. In the present invention, the fish scale gelatin composite film is modified by the combined action of silk fibroin, plasticizer and high dielectric constant dopant, which not only shows good thermal stability and hydrolysis resistance, as well as excellent tensile strength and repeated bending performance, but also significantly improves the output electrical performance of the friction nanogenerator, including voltage, current and power density. This ensures the stability and service life of the friction material of TENG under different environments.

[0019] 3. The present invention applies the modified fish scale gelatin / silk fibroin composite film and PDMS film to the friction material of the friction nanogenerator, which has high triboelectric efficiency, is non-toxic and harmless, has biocompatibility, high light transmittance, and excellent tensile strength, meeting the needs of wearable devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The drawings described herein are used to provide further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0021] in: Figure 1 This is a schematic diagram of the structure of a friction nanogenerator based on fish scale gelatin / silk fibroin composite film.

[0022] Figure 2 It is a comparison chart of the mechanical properties of fish scale gelatin composite films after adding silk fibroin in different proportions, and a comparison chart of the performance of fish scale gelatin composite films after adding high dielectric constant dopants in different proportions.

[0023] Figure 3 It is a comparison chart of TENG output performance of fish scale gelatin / silk fibroin composite film and PDMS film with and without surface microstructure.

[0024] Figure 4 This is a graph showing the relationship between the open circuit voltage / short circuit current and the size and pressing frequency of the friction nanogenerator based on fish scale gelatin / silk fibroin composite film.

[0025] Description of labels: 10. PI encapsulation layer; 20. Conductive copper foil tape; 30. Fish scale gelatin / silk fibroin composite film; 40. Elastomer support layer; 50. PDMS film. DETAILED DESCRIPTION

[0026] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer and more understandable, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. Example

[0027] This embodiment provides a method for preparing a triboelectric nanogenerator based on a fish scale gelatin / silk fibroin composite film, the structure of which is shown in the attached figure. Figure 1 As shown, from top to bottom, there are PI encapsulation layer 10, conductive copper foil tape 20, fish scale gelatin / silk fibroin composite film 30, elastomer support layer 40, PDMS film 50, conductive copper foil tape 20 and PI encapsulation layer 10. The specific steps are as follows: Step 1: Wash and dry the discarded fish scales for multiple times, weigh 40g of dry fish scales, and then treat the dry fish scales with 0.6M hydrochloric acid for 1h, rinse the treated fish scales with deionized water 10 times and soak them in deionized water for 1h, mix the treated fish scales with 120ml of deionized water and place them in a stainless steel sealed container for hydrolysis at a hydrolysis temperature of 100°C for 3h; Step 2: After the fish scales are hydrolyzed and cooled to 25°C, the solid and liquid are separated by a sieve, and the liquid filtrate is centrifuged at 10,000 rpm for 10 minutes to remove the solid residue, so as to prepare a fish scale gelatin aqueous solution; Step 3: After the silk cocoons are cut into pieces, the broken silk cocoons are weighed, deionized water is boiled and sodium carbonate or sodium bicarbonate powder is added, and after the silk cocoons are fully dissolved, the broken silk cocoons are added, and the boiling is maintained for 30 minutes, and the process is repeated three times to ensure that the sericin on the silk surface is fully dissolved, and after the degumming is completed, the silk fibers are rubbed three times with distilled water, and the degummed silk fibers are dried after being cleaned; Step 4: using 9.5M lithium bromide solution to dissolve silk fibers in a 60°C oven for 3 hours to obtain a silk fibroin solution, and then dialyzing the solution, changing the water every 2 hours for 2 days, and finally centrifugally filtering to obtain a clear and transparent silk fibroin solution; Step 5: The fish scale gelatin solution and the silk fibroin solution are mixed in different proportions, and then a plasticizer and high dielectric constant nanoparticles of different concentrations are added thereto and stirred evenly, and the mixed solution is poured into a mold with a microstructure on the surface, and dried at 60° C. for 1 hour to prepare a fish scale gelatin / silk fibroin composite film; Step 6: Attach conductive copper foil tape to the back of the fish scale gelatin / silk fibroin composite film and the PDMS film obtained in step 5 respectively and connect them with single-core multi-strand wires. Place the composite film and the PDMS film opposite to each other, place the PDMS elastomer in the middle as a supporting layer, and assemble them into a friction nanogenerator using a vertical contact-separation mode. Finally, place the assembled generator as a whole in a protective casing.

[0028] Preferably, the plasticizer selected in step 5 is glycerol.

[0029] Preferably, the high dielectric constant nanoparticles selected in step 5 are barium titanate nanoparticles.

[0030] Preferably, the mold with a microstructure on the surface selected in step 5 is made of materials including but not limited to silicone latex and metal materials, and its microstructure comes from a natural or artificial reverse template.

[0031] Preferably, the protective shell selected in step 6 is a polyimide (PI) packaging layer.

[0032] After preparing the fish scale gelatin / silk fibroin composite film according to steps 1 to 6, the tensile properties and dielectric constant of the composite film were characterized by a universal tensile machine and an LCR tester, respectively. Figure 2 Adding different amounts of silk fibroin and high dielectric constant nanoparticles can effectively improve the tensile properties and dielectric constant of the composite film, respectively.

[0033] Conductive copper foil tapes were attached to the backs of the prepared composite film and PDMS film respectively, and single-core multi-strand wires were connected.

[0034] The composite film and the PDMS film are placed opposite to each other, with a PDMS elastomer placed in the middle as a supporting layer, and a friction nanogenerator is assembled using a vertical contact-separation mode.

[0035] After assembling the friction nanogenerator according to steps 1 to 6, an electrometer is used to test the power generation performance (such as open circuit voltage) of the friction nanogenerator using different composite films.

[0036] After assembling the triboelectric nanogenerator according to steps 1 to 6, an electrometer is used to test the power generation performance (such as open circuit voltage, short circuit current and short circuit charge) of the triboelectric nanogenerator when adopting different contact-separation mode parameters. Figure 3 , the power generation performance of the generator can be regulated by changing the area of ​​the friction layer and the contact-separation frequency. Example

[0037] This embodiment is similar to the embodiment 1, but when preparing the friction nanogenerator, the second friction material PDMS film is replaced with a polyvinylidene fluoride (PVDF) film. The specific steps are as follows: Prepare fish scale gelatin / silk fibroin composite films according to steps 1 to 5.

[0038] Prepare the PVDF film, ensuring that its thickness is comparable to that of the PDMS film to maintain the structural integrity of the generator.

[0039] Conductive copper foil tapes were attached to the backs of the composite film and the PVDF film respectively, and single-core multi-strand wires were connected.

[0040] The composite film and the PVDF film are placed opposite to each other, with a PDMS elastomer placed in the middle as a supporting layer, and a friction nanogenerator is assembled using a vertical contact-separation mode.

[0041] The assembled generator is placed in a protective casing of a polyimide (PI) encapsulation layer.

[0042] After the fish scale gelatin / silk fibroin composite film and PVDF film were assembled into a triboelectric nanogenerator, the power generation performance (such as open circuit voltage) of the triboelectric nanogenerator under different friction pairs was tested using an electrometer. Figure 4 Compared with PVDF film, using PDMS film as a friction pair can effectively improve the power generation performance such as the open circuit voltage of the generator. Example

[0043] In this embodiment, when preparing the triboelectric nanogenerator, the high dielectric constant nanoparticle doping material is replaced with graphene or MXene. The specific steps are as follows: Fish scale gelatin / silk fibroin composite films were prepared according to steps 1 to 6, but in step 5, the high dielectric constant nanoparticles were replaced with graphene or MXene.

[0044] Conductive copper foil tapes were attached to the backs of the prepared composite film and PDMS film respectively, and single-core multi-strand wires were connected.

[0045] The composite film and the PDMS film are placed opposite to each other, with a PDMS elastomer placed in the middle as a supporting layer, and a friction nanogenerator is assembled using a vertical contact-separation mode.

[0046] The assembled generator is placed in a protective casing of a polyimide (PI) encapsulation layer. Example

[0047] In this embodiment, when preparing the friction nanogenerator, the composite film and the PDMS film with microstructures on the surface are replaced with a film with smooth surface and no structure. The specific steps are as follows: Fish scale gelatin / silk fibroin composite films were prepared according to steps 1 to 6, but in step 5, a composite film with a smooth surface was prepared using a mold without microstructures.

[0048] Prepare a PDMS film with a smooth surface.

[0049] Conductive copper foil tapes were attached to the back of the smooth surface composite film and the PDMS film respectively, and single-core multi-strand wires were connected.

[0050] The composite film with a smooth surface is placed opposite to the PDMS film, with a PDMS elastomer placed in the middle as a supporting layer, and a friction nanogenerator is assembled using a vertical contact-separation mode.

[0051] The assembled generator is placed in a protective shell of a polyimide (PI) encapsulation layer. The power generation performance (such as open circuit voltage) of the triboelectric nanogenerator using different composite films is tested using an electrometer. Figure 4 Compared with the composite film with smooth surface, the composite film with surface microstructure can effectively improve the power generation performance such as the open circuit voltage of the generator. The present invention is described above by way of example in conjunction with the accompanying drawings. It is obvious that the specific implementation of the present invention is not limited to the above-mentioned method. As long as various non-substantial improvements are made using the method concept and technical solution of the present invention, or the concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.

Claims

1. A friction nanogenerator based on fish scale gelatin and silk fibroin composite film, characterized in that: It includes a first friction material, a second friction material, a first electrode and a second electrode, wherein: The first electrode covers the back side of the first friction material, the second electrode covers the back side of the second friction material, and the first friction material and the second friction material are stacked face to face to assemble a vertical contact-separation friction nanogenerator for collecting mechanical energy and converting it into electrical energy; The first friction material is a composite film based on fish scale gelatin; The second friction material is a polydimethylsiloxane film.

2. The friction nanogenerator based on fish scale gelatin and silk fibroin composite film according to claim 1, characterized in that: The composite film regulates the mechanical and chemical stability of the composite film based on fish scale gelatin by adding silk fibroin with good mechanical and hydrolysis resistance, thereby forming a fish scale gelatin / silk fibroin composite film to improve the durability of the friction nanogenerator.

3. The friction nanogenerator based on fish scale gelatin and silk fibroin composite film according to claim 2, characterized in that: The composite film regulates the dielectric properties of the fish scale gelatin / silk fibroin composite film by doping with high dielectric constant nanoparticles, so as to improve the output performance of the friction nanogenerator.

4. The friction nanogenerator based on fish scale gelatin and silk fibroin composite film according to claim 3, characterized in that: The raw material of the fish scale gelatin comes from discarded fish scales, and the raw material of the silk fibroin comes from natural silkworm cocoons.

5. The friction nanogenerator based on fish scale gelatin and silk fibroin composite film according to claim 1, characterized in that: A flexible supporting layer is arranged between the first friction material and the second friction material to provide a gap and enhance resilience.

6. A method for preparing a friction nanogenerator, for preparing a friction nanogenerator based on a fish scale gelatin and silk fibroin composite film as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1: Wash and dry the discarded fish scales for multiple times, then soak and treat the fish scales using an alkali method, an acid method or an enzyme method, and then mix the treated fish scales with deionized water and place them in a stainless steel sealed container for hydrolysis at a temperature between 50 and 120° C.; Step 2: After the fish scales are hydrolyzed and cooled, the mixed solution is centrifuged to remove solid residues to prepare a fish scale gelatin aqueous solution; Step 3: Cut the silk cocoons into pieces, wash them in a boiling sodium carbonate or sodium bicarbonate solution, wash them with distilled water after degumming, and dry the degummed fibers; Step 4: dissolving silk fibers with lithium bromide solution, dialyzing the solution, and obtaining a clear and transparent silk fibroin solution after centrifugal filtration; Step 5: the fish scale gelatin aqueous solution and the silk fibroin solution obtained in step 2 are mixed in different proportions, a plasticizer and high dielectric constant nanoparticles of different concentrations are added thereto and stirred evenly, the mixed solution is poured into a mold, and a fish scale gelatin / silk fibroin composite film is prepared by a casting method; Step 6: Attach the back of the composite film and the PDMS film prepared in step 5 to the first electrode and the second electrode respectively and connect them with single-core multi-strand wires. Place the composite film and the PDMS film opposite to each other, place an elastomer in the middle as a supporting layer, and assemble them into a friction nanogenerator using a vertical contact-separation mode. Finally, place the assembled generator as a whole in a protective casing.

7. The preparation method according to claim 6, characterized in that: In step 6, a conductive copper foil tape is used as the first electrode and the second electrode to facilitate adhesion to the back of the composite film and the PDMS film and to lead out a single-core multi-strand wire.

8. The preparation method according to claim 6, characterized in that: In step 2, the high dielectric constant nanoparticles include but are not limited to barium titanate nanoparticles, graphene or MXene, and the doping amount thereof is 2-20‰ of the weight of the composite film.

9. The preparation method according to claim 7, characterized in that: A polyimide PI film is added to the outer layer of the conductive copper foil tape of the first electrode and the second electrode to ensure the long-term working performance of the friction nanogenerator by relying on the stability of the polyimide film and to utilize the elasticity of the polyimide film to help achieve the automatic separation of the upper and lower electrode pairs.